Live-High Train-Low Altitude Training on Maximal Oxygen Consumption in Athletes: A Systematic Review and Meta-Analysis - A Commentary - A Response to Commentary - Lancaster, K.; Smart, N.; Duke, J. W.; Chapman, R. F.; Levine, B. D. (International Journal of Sports Science and Coaching, 2012)
We quantified the effects of four different protocols of Live-high Train-low altitude training on maximal aerobic capacity. A systematic search of PubMed for published studies, up to July 2010 was performed using appropriate search terms. Eleven studies met inclusion criteria. Combined analysis showed athletes exposed to hypoxia had higher maximal oxygen consumption compared to those undertaking normoxic training, Weighted Mean Difference (WMD) 1.51 ml. kg-1.min-1 [0.44, 2.58, p=0.006]; hemoglobin (WMD) 0.57 mg/dl-1 [0.38, 0.75, p-1 [-3.03, -0.50, p=0.006], and peak exercise blood lactate (WMD) -3.03 mmol. L-1 [-4.57, -1.49, p=0.0001]. Studies utilizing minimum hypoxic exposure of 9.5 hours daily showed a significantly greater weighted mean difference in maximal oxygen consumption WMD 3.45 ml.kg-1.min-1[0.30, 6.60] p=0.03, in the hypoxic subjects. Protocols using altitudes between 2,500 to 3,500m for a minimum of 9.5 hours daily for at least 2 weeks elicited greatest performance effects.